Epidemiology of bloodstream infections and predictive factors of mortality among HIV-infected adult patients in Thailand in the era of highly active antiretroviral therapy - Sasisopin Kiertiburanakul (2018)
Few studies have described the pattern of bloodstream infections (BSI) among HIV-infected patients in the highly active antiretroviral therapy (HAART) era, particularly in resource-limited settings. A retrospective cohort study was conducted among 140 HIV-infected patients who had a positive blood culture from 2004-2008. Of the 140 patients, 91 (65z) were male with amean (SD) age of 38 (9.1) years and a median (IQR) CD4 cell count of 32 (9-112) cells/mm3. Community-acquired infection was detected in 89z of patients. The blood cultures contained Gram-negative bacteria, 40z; fungi, 24z; Mycobacterium spp., 20z; and Gram-positive bacteria, 16z. Common causative pathogens were Cryptococcus neoformans, 21z; Salmonella spp., 15z; and Mycobacterium tuberculosis, 12z. Common focal sites of infection were the central nervous system, 24z; respiratory tract, 20z; and gastrointestinal tract, 18z. CD4 cell count (OR, 0.61 per 50 cells/mm3 increment; 95zCI, 0.39-0.96; P = 0.031) was the only factor associated with mycobacterial or fungal BSI. The crude mortality was 21z. HAART (OR, 0.23; 95z CI, 0.01-0.77; P = 0.017), focal infection (OR, 0.31; 95z CI, 0.10-0.97; P = 0.044), and complication (e.g., shock) (OR, 9.26; 95z CI, 3.25-26.42; P < 0.001) were the predictive factors of mortality. In conclusion, opportunistic infections are still the leading causes of BSI among HIV-infected patients in the HAART era.